ANALISIS KINERJA SISTEM PEMUNGUTAN DAN PENGAWASAN PENERIMAAN PAJAK HIBURAN DALAM ISU KENAIKAN TARIF PAJAK HIBURAN (STUDI KASUS : BAPENDA KAB. NGANJUK) - Madona Yulenda; Hanif Yusuf Seputro (JURNAL ILMIAH EDUNOMIKA, 2024)
This research was conducted with the aim of analyzing the entertainment tax collection and supervision system carried out by the Nganjuk Regency Bapenda, finding out the truth of the issue of increasing entertainment tax rates, and knowing the entertainment tax revenue after the latest regulations. In this study, a qualitative method with a descriptive approach is used. The data collection methods applied to this study are interviews and documentation. The results of this study explain that the issue of tax increases is true and is widely discussed. So that it triggers a change in the entertainment tax rate. The latest tariff is applied as of January 2024. As a result, entertainment tax revenue and PAD revenue before and after the change in the entertainment tax rate triggered the revenue performance, both experienced ups and downs. This is due to the level of compliance from taxpayers. The Self Assessment system is a system implemented by the Nganjuk Regency Bapenda in the entertainment tax collection process. Then the entertainment tax revenue supervision system often encounters problems caused by irresponsible taxpayers. However, the bapenda has presented a solution to overcome this problem. Keywords : Entertainment Tax, Collection System, Revenue Staffing, Tax Rate